Reading to learn vs learning to read : an investigation into the difference in the reading process between purposeful re ading and reading to answer comprehension questions [mikrofilem] - 562031 Khairi Izwan Abdullah (1991)
Thesis (Master of Arts in Linguistics) -- University of Lancaster, 1990